Illuminating the Future: Danio Rerio as Game Changing Model for Vision Restoration - Sashiman, Gannerlapalli; Pujitha, S.Lakshmi; Gurulakshmi, B.; Rani, D.Velangini; Tony, D.Eswar; Nadendla, Rama Rao (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Danio-rerio model has emerged as a revolutionary tool in biomedical research, offering genetic similarity to humans, cost effective, rapid reproduction rates. With 70% of the human genes having the similarity with danio-rerio, this model has become as the instrumental in studying genetic disorders, drug discovery, disease modelling. This article talks about the advantages of this model compared to laboratory animals. This paper mainly focuses on the vision restoration by using this model. Blindness remains as the one of the most challenging medical conditions, with limited regenerative capacity in the human retina. However, danio-rerio possess a unique ability to regenerate the damaged retinal cells through the activation of the muller glial cells, offering a promising avenue for the vision restoration in the humans. This remarkable regenerative mechanism has fuelled cutting edge research aimed at developing novel therapies for retinal diseases such as macular degeneration and retinitis pigmentosa. This paper explores the regenerative potential of danio-rerio in curing blindness, highlighting the molecular pathways that drive retinal repair. Additionally, this explores the how these insights are being translated into the ground breaking gene and stem cell therapies for human eye diseases. By harnessing the regenerative power of danio-rerio, we move closer to a future where blindness may no longer be irreversible.